2018
DOI: 10.1093/ijnp/pyy034
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Related Kappa Opioid Receptor Agonists with Substantial Differential Signaling Bias: Neuroendocrine and Behavioral Effects in C57BL6 Mice

Abstract: BackgroundThe kappa opioid receptor system has been revealed as a potential pharmacotherapeutic target for the treatment of addictions to substances of abuse. Kappa opioid receptor agonists have been shown to block the rewarding and dopamine-releasing effects of psychostimulants. Recent investigations have profiled the in vivo effects of compounds biased towards G-protein-mediated signaling, with less potent arrestin-mediated signaling. The compounds studied here derive from a series of trialkylamines: N-subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 53 publications
3
36
0
Order By: Relevance
“…agonists (DiMattio et al, 2015;White et al, 2015;Dunn et al, 2018Dunn et al, , 2019Ho et al, 2018;Kaski et al, 2019;Mores et al, 2019). In addition, a recent paper showed low intrinsic efficacy, rather than G-protein bias, could explain the reduced respiratory side effects in MOPr agonists (Gillis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…agonists (DiMattio et al, 2015;White et al, 2015;Dunn et al, 2018Dunn et al, , 2019Ho et al, 2018;Kaski et al, 2019;Mores et al, 2019). In addition, a recent paper showed low intrinsic efficacy, rather than G-protein bias, could explain the reduced respiratory side effects in MOPr agonists (Gillis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, RB-64 is aversive in the conditioned place preference paradigm, albeit it does not involve b-arrestin-2 recruitment at the kappa receptor (White et al, 2015); however, RB-64 did not increase anhedonia in rodents as compared to vehicle in the ICSS paradigm (White et al, 2015). Recently, three KOPr agonists provided with different degrees of functional selectivity toward G protein-dependent signaling were characterized with regard to their neuroendocrine and behavioral effects (Dunn et al, 2018): KOPrdependent sedative effects elicited by these ligands were symmetrical to their ability to recruit b-arrestin2 at KOPr. Thus, taken together, these data support the hypothesis that downstream of KOPr activation, sedation, coordination impairment and anhedonia may be due to b-arrestin-2 recruitment and aversion possibly related, at least in rodents, to arrestin-independent p38MAPK activation (White et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, an accumulating body of evidence suggests that KOPr agonists produce antinociception and anti-itch effects via G protein-mediated signaling (Bruchas and Chavkin, 2010;Morgenweck et al, 2015) while their b-arrestin-2-dependent induction of p38MAPK leads to many of the relevant adverse consequences, including centrally mediated dysphoria Ehrich et al, 2015), potassium channel heterologous desensitization (Clayton et al, 2009), neuropathy-induced astrocyte proliferation and related hyperalgesia , sedation, and motor incoordination (Dunn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of nalbuphine as a treatment for the pruritus associated with neuraxial opioid use has not been approved by the FDA, it has nevertheless been used in this capacity. In fact, one study found that nalbuphine was a better treatment for MIS than either a placebo, a control, diphenhydramine, naloxone, or propofol in patients receiving neuraxial opioids for acute pain related to surgery or childbirth [31]. However, the mechanism underlying nalbuphine's antipruritic effects is still unclear.…”
Section: Discussionmentioning
confidence: 99%